History and Development of the Ancak Agung Tradition in Commemorating the Prophet's Birthday in Situbondo Regency 1992-2025 - Yusuf, Ahmad Efendi; Zuhdi, Achmad (Proceedings of International Conference on Islamic Civilization and Humanities, 2026)
This study analyzes the history and development of the Ancak Agung tradition in the commemoration of the Prophet Muhammad’s birthday (Maulid Nabi) in Situbondo Regency during the 1992–2025 period as a form of integration between Islam and local culture. This tradition originated within an agrarian society that interpreted agricultural products as symbols of gratitude and reverence for the Prophet Muhammad SAW. This research employed the historical method consisting of heuristics, source verification, interpretation, and historiography using the social construction approach of Peter L. Berger and Thomas Luckmann. Data were collected through interviews, observation, and documentation. The findings indicate that the Ancak Agung tradition is a historical construction resulting from the acculturation process between Islamic religious values and local culture. The tradition underwent institutionalization through the roles of religious leaders and support from the local government, and since 2011, it has developed into one of the cultural icons of Situbondo Regency. In addition to functioning as a religious ritual, Ancak Agung embodies the values of gratitude, strengthens social solidarity, and serves as a medium of cultural da‘wah that adapts to social changes. This tradition also contributes to reinforcing social cohesion and the cultural identity of the community. These findings affirm that the Ancak Agung tradition represents the integration of Islam and local culture and enriches the study of Islamic Civilization History, particularly in understanding the relationship between religion, culture, and social dynamics within society.